Individual approach to student’s computer-aided learning - Cherednichenko, Galina; Shkolna, Olena (My University, 2015)
It is well known that individual student’s attention is an essential component of effective education. Experienced teacher focuses on individual characteristics of students, which include psychological characteristics, and seeks an individual approach to each student. But what about a computer-aided learning, where direct student-to-teacher communication is minimized? For instance, the computer-aided learning is designed for self-tuition or for distance education.
Keywords: students; personalized; індивідуальний підхід; студенти; кафедра ділової іноземної мови та міжнародної комунікації; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка